Race and Displacement : Nation, Migration, and Identity in the Twenty-First Century - Simmons, Merinda, 1981-; Marouan, Maha, 1975- (Book collections on Project MUSE., 2013)
Race and Displacement captures a timely set of discussions about the roles of race in displacement, forced migrations, nation and nationhood, and the way continuous movements of people challenge fixed racial definitions. The multifaceted approach of the essays in Race and Displacement allows for nuanced discussions of race and displacement in expansive ways, exploring those issues in transnational and global terms. The contributors not only raise questions about race and displacement as signifying tropes and lived experiences; they also offer compelling.